212k views
3 votes
Factor the perfect-square trinomial in y = (x2 + 2x + 1) − 1− 1.
y = (x +
)2 − 1 −1

User Shiyan Xu
by
5.4k points

2 Answers

3 votes

♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️


y = ( {x}^(2) + 2x + 1) - 1


y = ({x + 1})^(2) - 1


y = ({x + 1})^(2) - ({1})^(2)

We're done now but I have something to tell...

##############################

Hint :


{a}^(2) - {b}^(2) = (a + b)(a - b)

##############################


y = ( \: (x + 1) + 1)( \: (x + 1) - 1) \\


y = (x + 2)(x)

♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️

User Sokol
by
5.4k points
4 votes

Answer:

1

Explanation:

User Dmitriy Kisil
by
5.7k points